171k views
4 votes
Write the equation of the table below.

y - 5 = -2(x - 6)
y - 5 = -2(x - 6)

y - 5 = 2(x - 6)
y - 5 = 2(x - 6)

y - 6 = 2(x - 5)
y - 6 = 2(x - 5)

y - 6 = -2(x - 5)

Write the equation of the table below. y - 5 = -2(x - 6) y - 5 = -2(x - 6) y - 5 = 2(x-example-1
User AbhinavD
by
5.7k points

1 Answer

4 votes

Answer:

equation: y = 2x - 7

Explanation:

Let equation be y = mx + c

m = (1-(-1))/(4-3) = 2

sub (4, 1):

1 = 2(4) + c

c = -7

This is a question on coordinate geometry. If you wish to venture further into it/understand this topic better, you may want to follow my Instagram account (learntionary), where I post some of my own notes on certain topics and also some tips that may be useful to you :)

User Bitclef
by
6.3k points